Teaching English to children with special educational needs Kraków: Wydawnictwo Naukowe UP, 2020 - Nowak, Sabina (Neofilolog, 2022)
Review: Teaching English to children with special educational needs Kraków: Wydawnictwo Naukowe UP, 2020